Meteorological observations and condensation nuclei measurements at the Princess Elisabeth Antarctica Research Station during three austral summers - Herenz, Paul; Wex, Heike; Mangold, Alexander; Laffineur, Quentin; Gorodetskaya, Irina V; Fleming, Zoë L; Panagi, Marios; Stratmann, Frank (Supplement to: Herenz, P et al. (2019): CCN measurements at the Princess Elisabeth Antarctica research station during three austral summers. Atmospheric Chemistry and Physics, 19(1), 275-294, https://doi.org/10.5194/acp-19-275-2019, 2018)
For three austral summer seasons (2013-2016, each from December to February) aerosol particles arriving at the Belgian Antarctic research station Princess Elisabeth (PE), in Dronning Maud Land in East Antarctica were characterized. This included number concentrations of total aerosol particles (N[CN]) and cloud condensation nuclei (N[CCN]), the particle number size distribution (PNSD), the aerosol particle hygroscopicity and the influence of the air mass origin on N[CN] and N[CCN]. In general N[CN] was found to range from 40 to 6700 cm^-3 with a median of 333 cm^-3, while N[CCN] was found to cover a range between less than 10 and 1300 cm^-3 for supersaturations (SS) between 0.1 and 0.7%. It is shown that the aerosol is Aitken mode dominated, being characterized by a significant amount of small, and therefore likely secondarily formed aerosol particles, with 94% and 36% of the aerosol particles smaller than 90 nm and ~35 nm, respectively. Measurements of the basic meteorological parameters as well as the history of the air masses arriving at the measurement station indicate that the station is influenced by both, marine air masses originating from the Southern Ocean and coastal areas around Antarctica (marine events - MEs) and continental air masses (continental events - CEs). CEs, which were defined as times when the air masses spent at least 90% of the time during the last 10 days over the Antarctic continent, occurred during 61% of the time during which measurements were done. CEs came along with rather constant N[CN] and N[CCN] values, which we denote to be Antarctic continental background concentrations. MEs however cause large fluctuations in N[CN] and N[CCN] with low concentrations likely caused by scavenging due to precipitation and high concentrations likely originating from new particle formation (NPF) based on marine precursors. The application of HYSPLIT back trajectories in form of the potential source contribution function (PSCF) analysis indicate, that the region of the Southern Ocean is a potential source of Aitken mode particles. On the basis of PNSDs, together with N[CCN] measured at a SS of 0.1%, median values for the critical diameter for cloud droplet activation and the aerosol particle hygroscopicity parameter were determined to be 110nm and 1, respectively. For particles larger than ~110nm the Southern Ocean together with parts of the Antarctic ice shelf regions were found to be potential source regions. While the former may contribute sea spray particles directly, contribution of the latter may be due to the emission of sea salt aerosol particles, released from snow particles from surface snow layers, e.g., during periods of high wind speed, leading to drifting or blowing snow. The region of the Antarctic inland plateau however was not found to feature a significant source region for CN and CCN measured at the PE station in austral summer.